Proceedings of the 2014 ACM International Symposium on Wearable Computers 2014
DOI: 10.1145/2634317.2634340
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the wearability of head-mounted devices from a human-centered perspective

Abstract: Extensive efforts have been dedicated to developing wearables, but existing solutions focus mainly on feasibility and innovation. Thus, although many devices are named 'wearable', users face some wearability issues. Previously adopted trial and error approaches have effectively produced wearables, but not focusing on human factors. Through an extensive analysis of online comments about head-mounted devices, this paper presents their problem space from a human perspective. The analysis of online comments from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Other research analyzed some of the complexities of applying human factors heuristics for interface design to authentication, and indicate the importance of social acceptability, learnability, and simplicity of authentication methods (Braz and Robert, 2006). Technologies worn on the head entail particular usability issues; in their analysis of user perceptions of headworn devices, Genaro et al identified design, usability, ease of use, and obtrusiveness among the top ten concerns of users, as well as qualitative comments around comfort and “looking weird” (Genaro Motti and Caine, 2014).…”
Section: Related Workmentioning
confidence: 99%
“…Other research analyzed some of the complexities of applying human factors heuristics for interface design to authentication, and indicate the importance of social acceptability, learnability, and simplicity of authentication methods (Braz and Robert, 2006). Technologies worn on the head entail particular usability issues; in their analysis of user perceptions of headworn devices, Genaro et al identified design, usability, ease of use, and obtrusiveness among the top ten concerns of users, as well as qualitative comments around comfort and “looking weird” (Genaro Motti and Caine, 2014).…”
Section: Related Workmentioning
confidence: 99%
“…in 3D modeling) to update the prototype. With our cardboard solution, we ensure flexibility with customization, adaptation and personalization to satisfy more users (Genaro Motti and Caine, 2014) without adding extra cost.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the 150 g (5.3 oz) weight of the SE (Syberfeldt et al, 2017). Furthermore, all the weight is on the same ear, creating an imbalance which strengthens the discomfort (Motti & Caine, 2014). In addition, participants reported a face cluttering problem.…”
Section: Echo To Others Studiesmentioning
confidence: 99%